Models and Techniques to Study Aortic Valve Calcification in Vitro, ex Vivo and in Vivo. An Overview - Bogdanova, Maria; Zabirnyk, Arsenii; Malashicheva, Anna; Semenova, Daria; Kvitting, John-Peder Escobar; Kaljusto, Mari-Liis; Perez, Maria del Mar; Kostareva, Anna; Stensløkken, Kåre-Olav; Sullivan, Gareth J; Rutkovskiy, Arkady; Vaage, Jarle (Frontiers in Pharmacology, 2022)
Aortic valve stenosis secondary to aortic valve calcification is the most common valve disease in the Western world. Calcification is a result of pathological proliferation and osteogenic differentiation of resident valve interstitial cells. To develop non-surgical treatments, the molecular and cellular mechanisms of pathological calcification must be revealed. In the current overview, we present methods for evaluation of calcification in different ex vivo, in vitro and in vivo situations including imaging in patients. The latter include echocardiography, scanning with computer tomography and magnetic resonance imaging. Particular emphasis is on translational studies of calcific aortic valve stenosis with a special focus on cell culture using human primary cell cultures. Such models are widely used and suitable for screening of drugs against calcification. Animal models are presented, but there is no animal model that faithfully mimics human calcific aortic valve disease. A model of experimentally induced calcification in whole porcine aortic valve leaflets ex vivo is also included. Finally, miscellaneous methods and aspects of aortic valve calcification, such as, for instance, biomarkers are presented.